CORRECTING A MINOR ERROR: A NEW NAME FOR A MARANTACEAE SPECIES FROM NEW GUINEA - Ian Turner (REINWARDTIA, 2022)
TURNER, I. M. 2022. Correcting a minor error: a new name for a Marantaceae species from New Guinea. Reinwardtia 21(2): 81‒82. — The new name, Phrynium cominsia I.M.Turner, and lectotype are published for Cominsia minor Valeton (Marantaceae)